Interleaved Floating Boost PFC Converter With Intrinsic Current Balancing - Nguyễn Chấn Việt; Nguyễn Đình Tuyên; Phan Quốc Dũng; Hồ Thanh Phương; Lê An Nhuận; Nguyễn Đặng Tài; Mông Thị Thảo Trang (Journal of Technical Education Science, 2025)
This paper presents a two-phase interleaved power factor correction (PFC) converter based on the interleaved floating boost (IFB) topology. The design employs a single current sensor, leveraging the natural power-sharing function between phases to minimize hardware complexity and reduce implementation costs. Unlike the conventional two-phase interleaved boost converter (2P-IBC), the IFB converter offers higher voltage gain and lower voltage stress on semiconductor components. These advantages contribute to significantly reduced switching losses, particularly under low-line input voltage conditions, making it an efficient and cost-effective solution for PFC applications. Additionally, the IFB topology substantially decreases input current ripple, enabling the use of a smaller inductor, which further enhances system efficiency, achieves the fast respond and reduces overall size and cost. The proposed converter is well-suited for applications requiring high efficiency and compact design. To validate its performance, detailed simulations of a 1.6 kW IFB PFC converter are conducted, demonstrating its effectiveness and advantages over conventional approaches.